The association between maternal malaria infection and poor birth outcomes in a remote community in Papua, Indonesia - Tri Wahyudi Iman Dantara; Deddy Christian Aritonang (Indonesian Pediatric Society, 2023)
Background Sikari is a remote district in Papua, Indonesia, which is malaria-endemic. Malaria infection during pregnancy has been linked to poor birth outcomes. Objective To evaluate for an association between malaria infection in pregnancy and birth outcome. Methods This cohort study compared the outcomes of newborns from mothers infected with malaria during pregnancy vs. uninfected controls. We included clinical data of 82 pregnant women from January to December 2020 at the Batavia Public Health Center, Sikari District, Mamberamo Raya, Papua. Malaria diagnosis was established based on the World Health Organization (WHO) criteria and positive rapid diagnostic tests. The maternal and infant characteristics analyzed were years of formal education, antenatal care (ANC) visits, gestational age, obstetric history, diagnosis of malaria, birth weight, APGAR score, and newborn mortality. Results Forty-six mothers (56.1%) were diagnosed with malaria during pregnancy, of whom 33 (71.7%) had tropical malaria, 7 (15.2%) had tertian malaria, and 6 (13.0%) had mixed malaria. Malaria infections of any type were associated with an increased risk of preterm birth (OR 5.34; 95%CI 1.10 to 25.91; P=0.04), low birth weight (LBW) (OR 49.00; 95%CI 28.62 to 838.89; P=0.00), newborn mortality (OR 13.86; 95%CI 0.76 to 251.37; P=0.04), and low 5-minute APGAR score (OR 23.65; 95%CI 1.34 to 416.61; P=0.03). Tropical malaria was associated with a higher risk of preterm birth (OR 5.44; 95%CI 1.06 to 27.86; P=0.04), LBW (OR 15.22; 95%CI 1.82 to 127.02; P=0.01), newborn mortality (OR 14.09; 95%CI 0.75 to 265.48; P=0.04), and low APGAR (OR 24.33; 95%CI 1.34 to 440.77; P=0.03). Mixed malaria was associated with a higher risk of LBW (OR 35.00; 95%CI 2.73 to 449.10; P=0.01) and low APGAR score (OR 40.56; 95%CI 1.67 to 985.39; P=0.02). Conclusion Malaria infections are associated with an increased risk of preterm birth, low birth weight, newborn mortality, and low 5-minute APGAR scores.